Screening 'Prufrock': What the Mermaids Sing. (16th February 2019) - Freer, Scott
Abstract: At least in theory, poetry, unlike other forms of fiction, does not offer the optimum starting point for successful cinematic adaptation. But this article examines two film adaptations of T.S. Eliot's modernist poem, 'The Love Song of J. Alfred Prufrock' (1915): Till Human Voices Wake Us (2002) and I Have Heard the Mermaids Singing (1987). Both screenings take their cue from the closing dream sequence when Prufrock imagines hearing mermaids sing, which on one level symbolizes a source of potential healing for the alienated male speaker. The female figures can be more critically read as a misogynistic projection of Prufrock's sexual neurosis and existential paralysis. The two films give form to Eliot's 'dreamy' poetics to offer a more optimistic understanding of what the mermaids' song means. In Human Voices, it is the Jungian anima in a drama of male trauma and emotional repression. In Mermaids, it is a gnostic aesthetic vision, which a female protagonist achieves despite alienation from a mainstream art world. To different degrees, these adaptations bring a queer perspective to the early modernist poem by altering the hetero-normative gender dynamics of the original. These films enter a profound inter-textual dialogue with Eliot's poem, and so constitute sophisticated examples of the enduring trans-media legacy of probably the most popular poem of the twentieth century.